2017
DOI: 10.1016/j.exger.2017.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Milk fat globule membrane supplementation with voluntary running exercise attenuates age-related motor dysfunction by suppressing neuromuscular junction abnormalities in mice

Abstract: Age-related loss of skeletal muscle mass and function attenuates physical performance, and maintaining fine muscle innervation is known to play an important role in its prevention. We had previously shown that consumption of milk fat globule membrane (MFGM) with habitual exercise improves the muscle mass and motor function in humans and mice. Improvement of neuromuscular junction (NMJ) was suggested as one of the mechanisms underlying these effects. In this study, we evaluated the effect of MFGM intake combine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
29
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 36 publications
3
29
1
Order By: Relevance
“…Second, dietary MFGM supplementation combined with VR attenuated aging-associated loss of muscle mass and strength in naturally aging mice, consistent with our previous findings in SAM mice (25). MFGM intake or VR alone did not significantly improve muscle mass and strength, which is in agreement with previous studies (29,(35)(36)(37). These results suggest that improvements in muscle characteristics that are associated with MFGM ingestion and VR depend on the synergism between these factors.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Second, dietary MFGM supplementation combined with VR attenuated aging-associated loss of muscle mass and strength in naturally aging mice, consistent with our previous findings in SAM mice (25). MFGM intake or VR alone did not significantly improve muscle mass and strength, which is in agreement with previous studies (29,(35)(36)(37). These results suggest that improvements in muscle characteristics that are associated with MFGM ingestion and VR depend on the synergism between these factors.…”
Section: Discussionsupporting
confidence: 92%
“…Considering the drastic decrease of time spent on the rotarod, in the present study, 20-to 21-mo-old mice were in the later phase of aging. On the other hand, severe NMJ abnormalities were rarely observed in the muscles of 14-moold mice in our previous study (29); therefore, mice of this age may be during the early phase of aging. In this study, we observed that the age-related reduction in Dok-7 levels in muscle was rescued by MFGM intake with VR in 21-mo-old mice.…”
Section: Discussioncontrasting
confidence: 46%
See 2 more Smart Citations
“…Thus far, there are no reports of glucosamine improving the active range of motion at any joint. However, there are reports of MFGM combined with light exercise improving muscle strength in both mice and humans (2)(3)(4)8) and improving motor coordination via the neuromuscular junction (20). The sphingomyelin contained in MFGM is thought to play a role in these effects (8).…”
Section: Discussionmentioning
confidence: 99%